Cost-effectiveness of inclisiran in patients with atherosclerotic cardiovascular disease from Chinese healthcare perspective - Mochou Liu; Xinyue Zhang; Mengwen Feng; Qingfeng He; Zhen Feng (PLoS ONE, 2026)
Background Atherosclerotic cardiovascular disease (ASCVD) imposes a substantial clinical and economic burden in China. Despite maximally tolerated statin therapy, many patients fail to achieve recommended low-density lipoprotein cholesterol (LDL-C) targets. Inclisiran, a novel small interfering ribonucleic acid (siRNA) therapy, provides sustained LDL-C reduction, but its economic value under the Chinese healthcare system remains uncertain. Objective To evaluate the cost-effectiveness of inclisiran when added to standard lipid-lowering therapy for patients with ASCVD in China. Methods A Markov cohort multistate-transition model was developed from the perspective of the Chinese healthcare system, using a one-year cycle length and a lifetime horizon. Clinical inputs, costs, and utilities were derived from published literature and clinical trials. Both costs and outcomes were discounted at 4.5% annually. The primary result of the economic evaluation was the incremental cost-effectiveness ratio (ICER), with inclisiran considered cost-effective if the ICER was below the willingness-to-pay (WTP) threshold of CNY 191,498 per quality-adjusted life year (QALY), equivalent to two times China’s per capita gross domestic product in 2024. One-way and probabilistic sensitivity analyses were conducted to assess model uncertainty. Results Compared with statin therapy alone, inclisiran added to statin therapy yielded an additional 0.41 QALYs and incurred incremental costs of CNY 58,321.35, resulting in an ICER of CNY 143,044.57/QALY, which is well below the WTP threshold. One-way sensitivity analyses showed that the mortality reduction effect, discount rate, and inclisiran price were the main drivers of model outcomes; however, inclisiran remained cost-effective across all tested scenarios. Probabilistic sensitivity analysis showed a 95.1% probability that inclisiran is cost-effective at the current price. Conclusions At its current negotiated price of CNY 2,790 per dose, inclisiran added to standard therapy is cost-effective for patients with ASCVD in China.